2005
DOI: 10.1021/ic051616y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Electrochemical Studies on [1.1]Ferrocenophanes Containing Aluminum, Gallium, and Indium

Abstract: The synthesis, characterization, structure, and electrochemistry of [1.1]ferrocenophanes, bridged by the heavier group 13 elements aluminum (1a), gallium (1b), and indium (1c), are described and discussed. Compounds 1a-c have been synthesized from dilithioferrocene and intramolecularly coordinated group 13 element dihalides Ar'EX(2) (Ar' = 2-(Me(2)NCH(2))C(6)H(4); EX(2) = AlCl(2), GaCl(2), InI(2)). Although the synthesis and characterization of 1a by single-crystal X-ray analysis has been described recently (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 30 publications
3
36
1
Order By: Relevance
“…[26][27][28] Boron-bridged oligo-and polyferrocenes are particularly intriguing owing to the opportunity to switch between tri-and tetracoordinate boron through the binding of nucleophiles, which in turn influences the degree of electronic communication between the ferrocene moieties. [28][29][30] An early example of a MV boron-bridged oligoferrocene is the zwitterionic borate Fc II 3 Fc III B (Fc= ferrocenyl), which features a tetra-coordinate boron bridge. Although an intervalence charge-transfer (IVCT) band was detected in the NIR region, a localized structure was identified in the solid state by X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Boron-bridged oligo-and polyferrocenes are particularly intriguing owing to the opportunity to switch between tri-and tetracoordinate boron through the binding of nucleophiles, which in turn influences the degree of electronic communication between the ferrocene moieties. [28][29][30] An early example of a MV boron-bridged oligoferrocene is the zwitterionic borate Fc II 3 Fc III B (Fc= ferrocenyl), which features a tetra-coordinate boron bridge. Although an intervalence charge-transfer (IVCT) band was detected in the NIR region, a localized structure was identified in the solid state by X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly little information is available on ferrocenylaluminum compounds. Recently, it has been shown that the reactions of 1,1 0 -dilithiated ferrocene fcLi 2 with organoaluminum dihalides afford ferrocenophanes with aluminum in the bridge, stabilised by intramolecular coordination [5,6], 1,1 0 -disubstituted ferrocene [7] or rather novel types of ferrocenylaluminum compounds [6b,8]. Ferrocenylmercury chloride reacts with trialkylalanes to give mixed dimers 2 [9].…”
mentioning
confidence: 99%
“…[20] Since the X-ray crystal structure of the first [1.1]ferrocenophane was reported by Watts et al in 1967, [52] such species have attracted significant attention, owing to their unusual structural and redox properties. [53] Analogous [1.1]ferrocenophanes bearing ER x bridging groups, in which E ranges from Group 13 (B, [54] Al, Ga, In [55] ), Group 14 (C [56] Si, [53,57] Sn [19] ) to Group 15 (P [58,59] ), have also been published and their properties extensively studied. Nonetheless, to the best of our knowledge, compound 10 is the first example of a Group- 16- [54,59] It has been previously noted that, in general, the greater the ring-strain in [1]ferrocenophanes, the more upfield shifted the ipso-Cp-C 13 C resonance.…”
Section: Resultsmentioning
confidence: 99%